CLIMATE-SMART AGRIBUSINESS AND DIGITAL TRANSFORMATION IN AGRICULTURAL ECONOMIES (Contemporary Journal of Social Science Review, 2026)
The global need for a sustainable agricultural transformation and resilient agribusiness systems has been amplified by the escalating impacts of climate change, environmental degradation, food insecurity and resource scarcity. In response to these challenges, climate-smart agriculture and digital transformation technologies are increasingly being integrated into agricultural economies to enhance productivity, sustainability, climate resilience, and rural economic development. In this qualitative study we critically examine how climate-smart agribusiness practices and digital technologies are transforming agricultural systems and impacting agricultural economies in developing and emerging regions. This research examines the opportunities, experiences and challenges of adopting digital and climate-smart agricultural strategies in modern-day agribusiness contexts. This study adopts a qualitative research methodology based on semi-structured interviews, thematic analysis, observational data, expert opinions, farmers’ experiences, and policy document analysis to explore the role of digital transformation in promoting sustainable agricultural development. The findings reveal that climate-smart agribusiness practices coupled with smart farming technologies, precision agriculture, digital monitoring systems and data-driven decisions significantly contribute towards enhanced agricultural productivity, efficient resource management, improved climate resilience and strengthened agricultural value chains. Participants also stressed the importance of digital innovation to improve market access, promote sustainable farming systems and support rural economic growth. However, the study also uncovers some structural and operational challenges related to digital transformation in agricultural economies, including limited technological infrastructure, financial constraints, unequal access to digital resources, low levels of digital literacy, policy limitations, and resistance to technological adaptation in farming communities. These results suggest that the successful integration of climate-smart and digital agricultural systems requires coordinated policy support and institutional investment, farmer education, technological accessibility and inclusive rural development strategies. The findings have important implications for policymakers, agribusiness organisations, agricultural institutions, sustainability experts and rural development planners who are interested in promoting environmentally sustainable, technologically adaptive and economically resilient agricultural systems. The study underscores the increasing importance of the convergence of climate-smart agriculture and digital transformation as the new paradigm for sustainable agricultural development, food security, and resilient agricultural economies in the changing global climate and digital environment.